2 answers:
Answer:
x =(k-c)/6
Step-by-step explanation:
6x + c = k
Subtract c from each side
6x + c -c = k-c
6x = k-c
Divide by 6
6x/6 = (k-c)/6
x =(k-c)/6
Answer:
x = ( k - c )/ 6
Step-by-step explanation:
6x + c = k
subtract c from both side
6x + c - c = k - c
simplify
6x = k - c
divide both side by 6
6x / 6 = ( k - c) / 6
x = ( k - c )/ 6
You might be interested in
Answer: It is 3 and negative -3
Step-by-step explanation:3 units away from zero forwards and back are both 3 but one is negative
Answer:
B-105.4 min
explanation
i just learned that just now
37.59
Just multiple .3 x 125.30
The gcf he can make is 131,313 packages